2016
DOI: 10.1039/c5nj03320a
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking of highly methoxylated pectin with copper: the specific anion influence

Abstract: Highly methoxylated pectin was cross-linked using different copper salts. The dependence between anion type, sorption capacity, mechanical and structural properties of obtained beads was found and correlated with Hofmeister theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…4). The broad band appeared at 3429 cm -1 in the spectra corresponds to the OH groups due to hydrogen intra-and intermolecular hydrogen bonding of pectin (Seslija et al 2016). The presence of alkyl group was observed by the existence of peak at 2921 cm -1 .…”
Section: Characterizationmentioning
confidence: 91%
“…4). The broad band appeared at 3429 cm -1 in the spectra corresponds to the OH groups due to hydrogen intra-and intermolecular hydrogen bonding of pectin (Seslija et al 2016). The presence of alkyl group was observed by the existence of peak at 2921 cm -1 .…”
Section: Characterizationmentioning
confidence: 91%
“…55 , and CH 3 COO −1 were used for crosslinking process of highly methoxylated pectin and copper concentration was measured in solution during crosslinking. al.…”
Section: In Vitro Release Studiesmentioning
confidence: 99%
“…al. 55 , and CH 3 COO −1 were used for crosslinking process of highly methoxylated pectin and copper concentration was measured in solution during crosslinking. They found that the anions affected the sorption capacity which implied greater/smaller exhaustion of the copper ions involved in the crosslinking process.…”
Section: In Vitro Release Studiesmentioning
confidence: 99%
“…Pectin consists of a long chain polysaccharide with D-galacturonic acid as its monomer which resides in an alpha-(1-4) chain. As a polysaccharide, it has a broad carboxylic O-H stretch from 3500 to 2400 cm −1 , a carbonyl C=O stretch at 1710 cm −1 , an asymmetric and symmetric carboxylic anionic vibration at 1637 cm −1 and 1549 cm −1 , a C-OH (carboxylic, ester, and alcoholic) stretch at 1047 cm −1 [ 32 ], and 1200–800 cm −1 for carbohydrates and in the fingerprint region.…”
Section: Resultsmentioning
confidence: 99%